The contributions of rainfall and fog to leaf water of tree and epiphyte communities in a tropical cloud forest - Yang, Qingqing; Zhang, Zijing; Zhang, Hui; Yang, Huai; Pandey, Shree; John, Robert (Frontiers in Plant Science, 2024)
Tropical cloud forest ecosystems are expected to face reduced water inputs due to climatic changes. Here, we study the ecophysiological responses of trees and epiphytes within in an Asian cloud forest to investigate the contributions of rainfall, fog, and soil to leaf water in 60 tree and 30 vascular epiphyte species. We measured multiple functional traits, and δ 2 H, and δ 18 O isotope ratios for leaf water, soil water, rainfall, and fog in the wettest (July) and driest (February) months. Using a Bayesian stable isotope mixing model, we quantified the relative contributions of soil water, fog, and rainfall to leaf water. Rainfall contributes almost all the leaf water of the epiphytes in July, whereas fog is the major source in February. Epiphytes cannot tap xylem water from host trees, and hence depended on fog water when rainfall was low.Most of leaf water was absorbed from soil water in July, while fog was an important source for leaf water in February despite the soil moisture content value was high. In February, lower temperatures, along with reduced photosynthesis and transpiration rates, likely contributed to decreased soil water uptake, while maintaining higher soil moisture levels despite the limited rainfall. These contrasting contributions of different water sources to leaf water under low and high rainfall and for different plant groups outline the community-level ecophysiological responses to changes in rainfall.While direct measurements of water flux, particularly in roots and stems, are needed, our results provide valuable insights on tropical cloud forest hydrology under scenarios of decreased fog immersion due to climatic changes.